Communication Strategies In Collaborative Learning : Analysis In Vocational Education - I Putu Gede Buda Mardiksa Putra; Ni Made Juliani; Alit Putrawan (PT. Anagata Sembagi Education, 2025)
Vocational Education is essential for the preparation of students into the workforce. Soft skills, such as communication, teamwork, and problem solving, are key to success in the work environment. Collaborative learning, which involves students actively cooperating, proves effective in developing skills. The study aims to explore the concepts of collaborative learning and the role of student cooperation in improving soft skills in Vocational Education. This research uses the study method of literature. Reviews are conducted on relevant scientific articles, books, and journals on collaborative learning in Vocational Education. The results of the study showed that collaborative learning significantly enhances communication skills, teamwork, and problem solving students. In addition, this approach also strengthens the interpersonal skills that are essential in professional and personal life. These findings provide important insights for the development of more holistic Vocational Education. Its focus includes technical skills and development of soft skills that are important in the workforce.